The importance of L1 ORF2p cryptic sequence to ORF2p fragment-mediated cytotoxicity. (3rd July 2016) - Christian, Claiborne M.; Kines, Kristine J.; Belancio, Victoria P.
ABSTRACT: The Long Interspersed Element 1 (LINE1 or L1) ORF2 protein (ORF2p) can cause DNA damage through the activity of its endonuclease domain (EN). The DNA double-strand breaks (DSB) introduced by the ORF2p EN have the potential to be mutagenic. Previously, our lab has shown that ORF2p fragments containing the EN domain could be expressed in mammalian cells and have variable cytotoxicity. Inclusion of the ORF2p sequence C-terminal to the EN domain in these fragments both reduced the cytotoxicity of these fragments and increased their presence in the nucleus as detected by Western blot analysis. Here, we identify the amino acids (aa 270–274) in the newly-identified ORF2p Cryptic region (Cry) that may be important to the subcellular localization and cytotoxic potential of these EN-containing ORF2p fragments.